PENGEMBANGAN PROGRAM PELATIHAN UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MEMFASILITASI KETERAMPILAN BERPIKIR KRITIS ANAK USIA DINI - Witarsa, Ramdhan (IKIP Siliwangi, 2015)
National Education Standards Agency (BSNP 2010) the Paradigm of National Education 21st Century stated that the strategy of educational attainment in the future one is to apply the methods of teaching and learning creative adhered to the principle that every individual isunique and has the talent of each, then teaching and learning methods should also pay attention to the diversity of